Pulmonary metastases of uterine endometrial stromal sarcoma in a young patient: An extreme rarity - Sonia Chhabra; Namita Bhutani; Sunita Singh; Monika Sangwan; Rajeev Sen (Elsevier, 2017)
Endometrial stromal sarcoma (ESS) is a rare malignant tumor of the endometrium, usually seen in perimenopausal females. We report a case of ESS in a 24 year old woman, presenting as rapid enlargement of a uterine fibroid associated with irregular and excessive vaginal bleeding along with a lung nodule. Hysterectomy was performed. Histopathological examination and immunohistochemistry confirmed ESS. A proper preoperative diagnosis is difficult and in most cases the diagnosis is confirmed after hysterectomy for a presumed benign disease. Simultaneous pulmonary metastasis of ESS is an extremely rare event. As the tumor is rarely encountered, management protocols are still questionable. Although rare, ESS should be considered in the differential diagnosis of all women who present with a rapid enlargement of a uterine leiomyoma. This report is aimed to present a case of endometrial stromal tumor in a young female with simultaneous lung metastasis because of its rare existence and difficulties in establishing histological diagnosis. Keywords: Endometrial stromal sarcoma, Immunohistochemistry, Lung metastasis, Malignant uterine tumor, Uterine leiomyoma